PnpM, a LysR-Type Transcriptional Regulator Activates the Hydroquinone Pathway in para-Nitrophenol Degradation in Pseudomonas sp. Strain WBC-3 - Wang, Jin-Pei; Zhang, Wen-Mao; Chao, Hong-Jun; Zhou, Ning-Yi (Frontiers in Microbiology, 2017)
A LysR-type transcriptional regulator (LTTR), PnpR, has previously been shown to activate the transcription of operons pnpA, pnpB, and pnpCDEFG for para-nitrophenol (PNP) degradation in Pseudomonas sp. strain WBC-3. Further preliminary evidence suggested the possible presence of an LTTR additional binding site in the promoter region of pnpCDEFG. In this study, an additional LTTR PnpM, which shows 44% homology to PnpR, was determined to activate the expression of pnpCDEFG. Interestingly, a pnpM-deleted WBC-3 strain was unable to grow on PNP but accumulating hydroquinone (HQ), which is the catabolic product from PNP degradation by PnpAB and the substrate for PnpCD. Through electrophoretic mobility shift assays and promoter activity detection, only PnpR was involved in the activation of pnpA and pnpB, but both PnpR and PnpM were involved in the activation of pnpCDEFG. DNase I footprinting analysis suggested that PnpR and PnpM shared the same DNA-binding regions of 27 bp in the pnpCDEFG promoter. In the presence of PNP, the protection region increased to 39 bp by PnpR and to 38 bp by PnpM. Our data suggested that both PnpR and PnpM were involved in activating pnpCDEFG expression, in which PNP rather than the substrate hydroquinone for PnpCD is the inducer. Thus, during the PNP catabolism in Pseudomonas sp. strain WBC-3, pnpA and pnpB operons for the initial two reactions were controlled by PnpR, while the third operon (pnpCDEFG) for HQ degradation was activated by PnpM and PnpR. This study builds upon our previous findings and shows that two LTTRs PnpR and PnpM are involved in the transcriptional activation of these three catabolic operons. Specifically, our identification that an LTTR, PnpM, regulates pnpCDEFG expression provides new insights in an intriguing regulation system of PNP catabolism that is controlled by two regulators.